Réponses

2013-05-11T12:21:10+02:00
G= (3x5a - 3x2) (1+4a) = (15a - 6) (1+4a) = 15ax1 + 15ax4a - 6x1 - 6x4a = 15a + 60a(avec a au carré) - 6 -24a. donc tu regroupes tout = 60a(au carré) - 9a -6
2013-05-11T12:21:40+02:00

1)

G = 3(5a - 2)(1 + 4a)

G = 3(5a + 20a² - 2 - 8a)

G = 15a + 60a² - 6 - 24a

G = 60a² - 9a - 6

 

2) Il suffit de remplacer x par deux valeurs de ton choix.

 

Si x = 1, alors :

G = 60a² - 9a - 6

G = 60*1² - 9*1 - 6

G = 60 - 9 - 6

G = 45

 

Si x = 2 alors

G = 60a² - 9a - 6

G = 60*2² - 9*2 - 6

G = 60*4 - 18 - 6

G = 240 - 18 - 6

G = 216